KEPATUHAN WAJIB PAJAK UMKM DI MASA SEBELUM DAN SAAT TERJADINYA PENDEMI COVID 19 - Hendrik Suhendri; Nur Ida Iriani; Efriani Aswani Tanggu (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
The financial condition of MSME actors before and during the Covid-19 pandemi is expected to affect the compliance of MSME actors in paying taxes. The purpose of this study was to determine the implications of the financial condition of MSMEs before and during the Covid-19 pandemi on MSME taxpayer compliance in Tlogomas Village, Lowokwaru District, Malang City. The sample with criteria and Slovin formula test obtained at least 32 respondents. The results of the data normality distribution test using the Shapiro Wilk Test showed the value of each financial data before and during the Covid19 pandemi was 0.024 and 0.025 (below 0.05). Furthermore, the results of the normality test of MSME taxpayer compliance data before and during the Covid-19 pandemi were 0.000 and 0.000 (below 0.05). The results of the Wilcoxon Signed Ranks Test show that there is a significant difference between financial conditions, which is 0.000 (below 0.05), meanwhile, the value of the Wilcoxon Signed Ranks Test for taxpayer compliance was 0.003 (below 0.05). Thus, it can be concluded that: (1) The stable financial condition of MSME actors before the Covid-19 pandemi tends to increase MSME actors' compliance in paying taxes. (2) The unstable financial condition of MSME actors during the Covid-19 pandemi tends to reduce MSME taxpayer compliance in fulfilling their tax obligations